Labor and Poverty. Women heads of households in Rural Areas of the Northeast and South of Brazil - de Oliveira, Nadja Simone Menezes Nery; Staduto, Jefferson Andronio Ramundo; Kreter, Ana Cecília de Medeiros Nitzsche; Darr, Dietrich (Sociedad y Economía, 2020)
This paper aims to analyze the profile of women heads of households in families residing in rural areas of Brazil and the northeast and south regions, from the personal, family and labor traits, and to discuss them according to the conditions of poverty and vulnerability. To do so, a descriptive statistical analysis was made based on the data of the Nacional por Muestras de Domicilios (PNAD) of the year 2014. It was verified that most of the women heads of households lived without their spouses or partners. The lack of contribution to a pension scheme suggests that a high percentage of women have an informal job. It is concluded that the women heads of households, regardless of the region they live in, is poorer than the men heads of households, and that the vulnerability of the women is stronger in the Northeast.